The Need for Enemies. (14th October 2014) - Fergusson, Leopoldo; Robinson, James A.; Torvik, Ragnar; Vargas, Juan F.
Abstract : We develop a model where some politicians have an edge in undertaking a task and this gives them electoral advantage, creating an incentive to underperform in the task. We test the empirical implications in the context of fighting against insurgents, using Colombian data. The main prediction is that large defeats for the insurgents reduce the probability that these politicians fight them, especially in electorally salient places. We find that after the largest victories against FARC rebels, the government reduced its counterinsurgency efforts, especially in politically important municipalities. Politicians need to keep enemies alive in order to maintain their political advantage.